DINAMIKA KEBIJAKAN PROGRAM PENGEMBANGAN PERTANIAN DI INDONESIA - Febrianto Syam, (Madika: Jurnal Politik dan Governance, 2022)
This article will look at the dynamics of agricultural development program policies in Indonesia. By taking studies on agricultural sector development policies, such as soybeans. Using a public policy approach with incremental analysis and cost analysis. The article attempts to capture a portrait of the dynamics of agricultural sector policies, especially in the aspect of commodity prices that experience fluctuations. Using qualitative methods, relying on secondary data sourced from various official reports that have been issued by the government and private institutions that have credibility. The main argument of the article, sees that the extent to which development policies in the agricultural sector have shown a positive trend. Although for certain parts there are still many shortcomings. Political support is very much needed to create public agricultural policies that are pro-sector development